Tendências de incidência e mortalidade por câncer de mama em Fortaleza - Silva, Eduardo Henrique Cronemberger Costa e (2019)
Cancer is the second leading cause of death in the world, and, among women, breast cancer accounts for the highest incidence and mortality, especially in low- and middle-income countries. Temporal trends analysis helps to anticipate future situations based on past series. This study aimed to describe the characteristics of the population and to analyze breast cancer trends in incidence and mortality in Fortaleza between 1990 and 2015. Data from cancer registries, mortality system and census population were used in the period of 20 years for incidence analysis (1990-2009) and 25 years for mortality analysis (1990-2015). Crude and age-standardized rates of breast cancer incidence and mortality were calculated and the joinpoint regression model was applied to indicate trends. Between 1990-2009, 10776 new cases of breast cancer were diagnosed, of which 96.4% were invasive neoplasms. The most affected age groups were 40-49 and 50-59 and the median age was 54 years-old. The study identified age-standardized incidence rates (ASR per 100,000) variations along the period from 59.38 at the beginning (1990-1994) to 53.23 at the end (2005-2009) and ASR mortality variation from 13.23 (1990-1994) to 15.16 (2010-2015). The incidence trend of invasive breast cancer was steady in the period, with a non-significant Annual Percent Change (APC) of 0.8 (95% with Confidence Interval or CI -0.2-1,8). The model identified significant incidence trends, such as an increased incidence trends in premenopausal (<45 years) between 1992-1999, with APC=12 (95% CI 6.0-18.4), and in postmenopausal (55-64 years) between 1990-1995, with APC=14.5 (95% CI 7.7-21.6), followed by a significant reduction between 1995-2009, with APC= - 3.9 (95% CI -5.9 -1.8). Breast cancer mortality increased significantly in the period with APC = 0.3 (95% CI 0.1-0.5), mainly in premenopausal (<45 years) with APC = 1.7 (95% CI 0.6-2.8) and perimenopause (45-54 years) with APC = 2.1 (95% CI 1.3-2.9). The mortality trend was steady in postmenopausal women (55-65 years). In conclusion, invasive breast cancer incidence and mortality rates in Fortaleza in this study has followed a pattern common in other less developed regions of the world. Despite the steady trend in incidence, the observed increase in breast cancer mortality, especially in young women, should guide the health public policies to improve attention to this population.